KETERKAITAN KUALITAS TATA KELOLA KORPORASI, IMPLEMENTASI PRINSIP ETIKA BISNIS DAN POTENSI KECURANGAN PELAPORAN KEUANGAN - Muhammad A. Nuryatno (Media Riset Akuntansi, Auditing & Informasi, 2010)
The purpose of this research is to make clear the phenomena about the relationship between the likelihood of the financial reporting fraud, the implementation of business ethics principles and the quality of corporate governance. The objective of this research is to test empirically about them, based on auditors’ perception. The method used or the detailed of the study are: the nature of the study was hypothesis testing; the type of investigation used was causal relationship; the extent of researcher interference was minimal; the environment where the research undertaken was field experiment; unit of analysis was individual, ie. the Public Accountants; and the frequency of gathering the necessary data was one-shot or cross-sectional. The source of data was Indonesia Public Accountants which formed as population, and the sample were determined by purposive sampling method. Sample data were collected using questionnaire circulated by mail and research assistants. Data analysis was conducted by Structural Equation Modeling (SEM). The results showed some empirical evidences : According to auditors’ perception, the likelihood of financial reporting fraud are (is) affected by client’s corporate governance quality and/ or implementation of the business ethics principles. Based on those results, it is suggested: First, to the next researcher, to study the relationship between financial reporting fraud and oversight committee, such as risk management and/ or nomination committee. Second, to the management, to minimaze the financial reporting fraud by strengthening the quality of corporate governance and implementation of business ethics principles.